THE EFFECT OF CONSUMER PERCEPTIONS OF PRODUCTS AND MOTIVATION ON PURCHASE DECISIONS CANAKO RICE BOX WITH A LIFESTYLE AS A MODERATION VARIABLE - Anggita Rizki Defiani Hasibuan; Arlina Nurbaity Lubis; Parapat Gultom (CV. Radja Publika, 2023)
This study aims to determine and analyze the influence of consumer perceptions of the product and motivation on purchasing decisions for canako rice boxes with lifestyle as a moderating variable. The population in this study is the people of Medan City with 6 sub-districts including the sub-districts of Medan Barat, Medan Baru, Medan Polonia, Medan Johor, Medan Kota, Medan Selayang. The reason for using only 6 Medan Districts is that in terms of the distance from the Canako Rice Box outlet to the 6 Districts it is not too far away. The sampling technique in this study was non-probability sampling as many as 138 respondents. The data analysis method uses Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results of the study show that consumer perceptions of products have a positive effect on purchasing decisions. Motivation influences and is significant on purchasing decisions. Lifestyle moderates consumer perceptions of products on purchasing decisions. Lifestyle moderates between motivation and purchasing decisions.